Analisis Stakeholder Dalam Pengembangan Potensi Wisata Kampung Kemasan Di Kabupaten Gresik - Putri Kamtono, Amanda; Anggraeny Puspaningtyas; Supri Hartono (Public Administration Dept, Faculty of Social and Political Science, 2026)
This study aims to analyze the role of stakeholders in the development of tourism potential in Kampung Kemasan, Gresik Regency. The development of cultural-based tourism requires the involvement of various stakeholders with different levels of interest and influence; therefore, stakeholder analysis is needed to identify their roles and contributions. This study uses a qualitative approach with data collected through interviews, documentation, and literature review. Stakeholders are classified into four categories: key players, context setters, subjects, and crowd. The results show that stakeholders involved include government institutions, local communities, and supporting groups. The Department of Tourism, Bappeda, and DCKPKP act as key players in planning and implementing tourism programs. Meanwhile, the Department of Transportation, Environmental Agency, Satpol PP, and Diskoperindag function as context setters by supporting policies and infrastructure. Local communities, Pokdarwis, and community groups are categorized as subjects, while others are classified as crowd. Based on visitor data from 2021 to 2025, the number of tourists has increased significantly each year, indicating a positive impact of tourism development. However, coordination among stakeholders still needs improvement. In conclusion, the success of tourism development in Kampung Kemasan is influenced by stakeholder synergy. Strengthening coordination and community empowerment is essential for sustainable tourism management.